ORGANIC STERILIZATION SYSTEM (OSS) EFFECT IN NUTRITIONAL AND FUNCIONAL PROPERTIES OF YACON (Smallantus sonchifolius Poepp. & Endl.) - Guevara Pérez, Américo (2017)
The maximum chemical and functional conservation of the yacón by the organic sterilization system, was achieved by applying a load of 4 kg / pouch, 1 min. process time and temperature 100 °C saturated steam injection. Under these conditions, was obtained 2,4 % (db) protein and 52 % (db) of fructooligosaccharides. Regarding the microbial load, 60,59 % (10 CFU / g), 65,76 % (20 CFU / g) and 0 % (<10 CFU / g) for aerobes, molds, and yeasts, respectively decreased; pathogenic behavior was very similar to that of the raw material: E. coli <3 CFU / g, absence of Salmonella (25 g) and <3 CFU / g for total coliforms, whose samples were able to adjust to the demands of the health standard Peruvian and international standards; which showed that applying the OSS technology is accomplished to preserve the nutritional and functional quality of yacon.